Pengaruh Kombinasi Jus Tomat (Lycopersionesculentum Miil) dan Kurma (Phoenix Dactylizat L.) pada Kadar Hemoglobin - Chaerunisa Fitriyani; Dewi Andang Prastika; Heny Rosiana (Midwifery Care Journal, 2025)
Adolescent girls are significant because if the growth and development process at that time is optimal, it will produce healthy adolescent girls and in the end, it will produce healthy mothers to be as well. Adolescents tend to want to have an ideal body so neglect a healthy diet, followed by dense adolescent activities that make adolescent girl potentially experience health problems such as anemia so that researchers innovate drinks in the form of tomato juice and dates to increase hemoglobin levels apart from supplementation Fe. The type of this research is quantitative research. Quasi-experimental research design with pre-test design and post-test design with a control group. The sample in this study was Semarang Poltekkes students who lived in Semarang Poltekkes Dormitory and were aged 17-21 years and not menstruating. The sampling technique is by using purposive sampling techniques. The data analysis used is using an independent sample t-test. The results showed that there was no significant (p=0,309) effect of giving a combination of tomato and date juice on hemoglobin levels in adolescent girls. However, there was an increase in average hemoglobin levels before and after the intervention of juice and iron suplementation. The results of this study are expected that adolescent girls obediently consume Fe tablets according to the provisions. Apart from supplementation, young women can also consume fruits that contain iron such as dates, and contain vitamin C such as tomatoes to help absorb iron.